Faktor-faktor yang Mempengaruhi Tingkat Literasi Keuangan Syariah Mahasiswa Aktif Fakultas Ekonomi dan Bisnis Islam UIN Sunan Kalijaga Yogyakarta - Norlia; Auratul Atifah Harbit (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
Students are a priority target for the Financial Services Authority (OJK) education program aimed at promoting financial literacy in the general public. The objectives of this research are (1) to identify factors influencing the level of financial literacy among students in the Faculty of Islamic Economics and Business, and (2) to assess the level of Sharia financial literacy among students. The research method employed is quantitative research with descriptive analysis using quantitative data. The software used for data management includes Smart PLS 4.0, Microsoft Excel, and SPSS 22. Data will be analyzed using Structural Equation Modeling (SEM). The research results indicate that GPA (Grade Point Average) only significantly affects the attitude variable; gender does not significantly affect knowledge and attitude variables; education only significantly affects the attitude variable, while age aligns with the established hypotheses and is the only variable consistent with the research. Age not only has a positive effect on knowledge but also significantly influences the attitude variable toward financial literacy. The level of Sharia financial literacy among active students in the Faculty of Islamic Economics and Business (FEBI) at UIN Sunan Kalijaga Yogyakarta is 61.5% and classified as sufficiently literate. Significant factors influencing Sharia financial literacy among active FEBI UIN Sunan Kalijaga Yogyakarta students are age, GPA, and educatio.